Rapid Cost Estimation for Storms Recovery Using Geographic Information Systems. Issue 1 (2nd January 2016) - Berríos-Montero, Rolando A.; Stuban, Steven M. F.; Dever, Jason
Abstract : The present study introduces a new approach to estimate the recovery costs of public property in the aftermath of a storm, by integrating geographic information systems. Estimating recovery costs for a disaster is a current concern for emergency responders. This work focuses on applying economic indicators, population, and storm event tracking to geographic information systems for rapidly estimating recovery costs. Firstly, recovery costs of historical events are normalized and adjusted for inflation, wealth, and population. Geospatial analysis is used to predict, manage, and learn political boundaries and population density. Secondly, rapid recovery cost estimation is accomplished by defining population, personal income, and gross domestic product. Finally, a jurisdiction fiscal capacity is calculated illustrating the economic capability of jurisdictions to finance public property recovery based on their economy size. The variability of estimated absolute errors between cost estimates and actual normalized costs are also examined. Our results reveal that jurisdiction fiscal capacity is a more suitable metric for rapidly estimating recovery costs of public properties than the method presently followed by the Federal Emergency Management Agency. This new approach effectively aids the local government providing quick cost guidance to recovery responders, while offering the ability to construct accurate recovery cost.